Efecto de cinco moléculas químicas para control de sinfilidos en el cultivo de piña (Ananas comosus) MD2 - Montaño Romero, Hugo Eliecer (2014)
The present investigation had for object, to evaluate that of effect of five chemical molecules for sinfilidos control in the pineapple cultivation (Pineapples comosus) MD2. The applied insecticides were: Clorpirifos 9.0 l/ha-1 (witness), Deltametrina 3.0 l/ha-1, Cipermetrina 3.0 l/ha-1, Thiametoxan 2.5 l/ha-1, Ql Agri35 20.0 l/ha-1. Was carried out in the Ríos' county, Buena Fe canton, Km. 35 via Sacred Domingo Enclosure San Cristóbal, country property Altamira located in the coordinated UTM: 17M 0677960 - 9921924, had duration of 8 weeks. The design experimental employee was a D.B.C.A. (Design of Complete Blocks at random) with 5 treatments and 4 repetitions. The treatment T2 in which Deltametrina was applied to reason of 3 l/ha-1 is the one that presents smaller sinfilidos population and the smallest root damage. The economic analysis demonstrates that the treatment of smaller application/ha-1 cost with a value of U$D 79,05 are the treatment T3 in which Cipermetrina is applied (3.0 l/ha-1).